CREATING VIDEO AND SPEAKING ACHIEVEMENT IN EFL CLASSROOM - Alfha Desiana Maria (Universitas PGRI Palembang, 2017)
The aim of this paper were to share “Creating Video and Speaking Achievement in EFL Classroom”, to find out factors causing low ability in speaking class, to identify the effectiveness of videos in proficiency, to describe the effectiveness of videos in increasing students’ motivation in the speaking class, and to create a video project in speaking class. The research used qualitative method. The data of the research were collected using: interview, observation, and documentation. The data collected were classified into two major data; reflective notes and document analysis. The results showed that video project was the effective technique to improve students’ speaking achievement. Students showed enthusiasm in joining class. The video entertained and motivated them to get involved in creating a video project.Key words: Creating Video,Speaking Achievement